2020
DOI: 10.1101/2020.04.30.070789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Manipulation of the human tRNA pool reveals distinct tRNA sets that act in cellular proliferation or cell cycle arrest

Abstract: Different subsets of the tRNA pool in human are expressed in different cellular conditions. The "proliferation-tRNAs" are induced upon normal and cancerous cell division, while the "differentiation tRNAs" are active in non-dividing, differentiated cells. Here we examine the essentiality of the various tRNAs upon cellular growth and arrest. We established a CRISPRbased editing procedure with sgRNAs that each target a tRNA family. We measured tRNA essentiality for cellular growth and found that most proliferatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Induction of a Proliferation tRNA Signature Is Followed by Relaxation at the Differentiation Phase. We next set to examine what the changes are in the tRNA pool and if they correspond to the changes in demand as reflected by the codon usage, adapting a recently developed tRNA sequencing protocol (26) [see Materials and Methods for further details and Aharon-Hefetz et al (8) for additional quality assessment]. In the downstream analysis, we grouped together read counts of all tRNAs of the same anticodon that have at least a minimal tRNAScan prediction score [tRNAscan-SE (27)] above 50.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of a Proliferation tRNA Signature Is Followed by Relaxation at the Differentiation Phase. We next set to examine what the changes are in the tRNA pool and if they correspond to the changes in demand as reflected by the codon usage, adapting a recently developed tRNA sequencing protocol (26) [see Materials and Methods for further details and Aharon-Hefetz et al (8) for additional quality assessment]. In the downstream analysis, we grouped together read counts of all tRNAs of the same anticodon that have at least a minimal tRNAScan prediction score [tRNAscan-SE (27)] above 50.…”
Section: Resultsmentioning
confidence: 99%
“…To determine which modifications can be detected using tRNA-seq we crossed annotated modification positions from the MODOMICS database (9), with tRNA-sequencing data collected in this study and human (8) and Escherichia coli (38) data from previous studies. We found that out of 46 modification types annotated in MODOMICS for the indicated species, 13 modifications were detected based on mismatches or RT abortions in our protocol (SI Appendix, Fig.…”
Section: ]) (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 ) is further supported by data showing that the tRNA-ome expressed is reflective of the proliferative status of tissues [ 48 ]. Subsequent work has shown that by targeting individual tRNA families with the CRISPR-Cas9 system, most of the identified proliferation-promoting tRNAs were essential in rapidly dividing cells, with the tRNAs associated with differentiation showing higher essentiality in cells with a slower doubling time [ 96 ]. Although these differences could be assigned to the proliferative state of the cell, it seemed that the cellular origin was also an important factor [ 96 ].…”
Section: Mechanisms That Coordinate the Response To Codon Optimalitymentioning
confidence: 99%
“…In particular, mRNAs corresponding to cell-autonomous functions, related to proliferating cells, are enriched with a specific set of codons, while mRNA of multicellular functions, related to non-dividing cells, are enriched with a different set of preferred codons. The tRNA pool in these cells is dynamically regulated and its dynamics corresponds to the changes in codon usage, as also reflected in differential tRNA essentiality in proliferation and cell arrest 7,8 . Following these observations, it is essential to explore how does the tRNA pool change in a natural proliferation process, and what are the contributions of the tRNA pool regulation to the integrity dynamics and of the immune response.…”
Section: Introductionmentioning
confidence: 99%